Influence of microwave power and pulse ratio on color, sensory attributes, and microstructure of potato slices during intermittent microwave – hot-air drying - Jalal Dehghannya; Mahdi Habibi-Ghods (Journal of Agriculture and Food Research)
Pulsed microwave drying has gained substantial recognition due to the production of high-quality dried food products. Based on the available sources, joint alternating microwaves at a fixed “off” time with convective hot air drying at low temperatures has not been investigated. In this research, simultaneous effect of microwave power (0 (control: hot air), 360, 600, and 900 W) and pulse ratio (1 (continuous), 2, 4, and 6) were investigated on qualitative characteristics of potato slices including color, sensory, and microstructural attributes. The 360-W treatment with a pulse ratio 6 demonstrated better color considering lower total color change, less browning index, and higher transparency (chroma index) compared to other treatments. This result was attributed to decreased Maillard reaction rates due to lower drying temperatures. According to sensory panel evaluations, the 900-W treatment with a pulse ratio 1 was more preferred than other treatments in terms of crispness, hardness, chewability, and texture. Additionally, dried potatoes at 900 W and a pulse ratio 6 illustrated less microstructural collapse, featuring larger and more regular pores, reduced shrinkage, and consequently increased porosity. Generally, the findings confirmed that potato chips can be produced with suitable qualitative characteristics if the right power and pulse ratio are selected.